A Comparison of Warm and Cold Compresses for Reducing Menstrual Pain (Dysmenorrhea) among Female Adolescents - Wahyuni; Siti Khadijah; Aprila Yensi (Jurnal Kesehatan Cendikia Jenius, 2025)
Dysmenorrhea is pain that occurs before and during menstruation caused by a decrease in progesterone hormone, stress, menarche before age 12, family history, menstrual cycle duration, lack of exercise, and consumption of fast food, which can interfere with adolescents' activities. In Indonesia, it is estimated that 64% of women of reproductive age experience dysmenorrhea, and in West Sumatra, about 57.3% of women experience it. Dysmenorrhea management can be pharmacological or non-pharmacological. Non-pharmacological pain management is safer as it does not cause side effects, such as using warm or cold compresses. The purpose of this study was to compare the effectiveness of warm and cold compresses in reducing menstrual pain (dysmenorrhea) among female adolescents in Payakumbuh City in 2024. This research used an experimental design with a quasi-experimental approach and a two-group pre-test and post-test design. The sample consisted of 62 respondents selected using convenience sampling. Data were analyzed using univariate and bivariate analysis with the Mann-Whitney test. The results showed that among the 62 respondents, the average pain scale before applying a warm compress was 4.52, which decreased to 0.87 after applying the warm compress. The average pain scale before applying a cold compress was 4.68, which decreased to 0.90 after applying the cold compress. Statistical analysis using the Mann-Whitney test yielded a significance value of 0.880 (>0.05), indicating no significant difference between warm and cold compresses in reducing menstrual pain (dysmenorrhea) among female adolescents in Payakumbuh City in 2024. It is recommended that adolescent girls experiencing dysmenorrhea perform warm and cold compress therapy independently, as this can help reduce the consumption of pain-relieving medications.